2012
DOI: 10.1007/s00125-012-2526-0
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cancer (2): evaluating the impact of diabetes on mortality in patients with cancer

Abstract: In this paper we address methodological aspects of aetiological importance in the link between diabetes and mortality in patients with cancer. We identified nine key points on the cancer pathway at which confounding may arise-cancer screening use, stage at diagnosis, cancer treatment selection, cancer treatment complications and failures, peri-treatment mortality, competing risks for long-term mortality, effects of type 2 diabetes on anti-cancer therapies, effects of glucoselowering treatments on cancer outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 77 publications
2
97
0
Order By: Relevance
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Another study showed that individuals with diabetes and recent HbA 1c values >9.0% (75 mmol/mol; OR 1.5; 95% CI 1.3, 1.7) had higher mortality than those with recent 'normal' HbA 1c values between 6.5% (48 mmol/mol) and 9% (75 mmol/mol) [18]. Thus, the drop in MPR observed among patients with cancer in our study might have negatively influenced survival via the aforementioned mechanisms and may (partly) explain the established association between diabetes, cancer and survival [1][2][3].…”
Section: Discussionmentioning
confidence: 56%
“…Although the impact of cancer was more pronounced among cancers with a worse prognosis and among those with more advanced TNM stages, the difference in prognosis associated with these cancers seemed to only partly explain the impact of cancer on medication adherence. The decline in adherence seen among users of GLDs with cancer might negatively affect survival and (partly) explain the established association between diabetes, cancer and survival [1][2][3]. In future studies, the reason for the decline in MPR needs to be further elucidated among the different cancer types-is it the patient who prioritises the fight against cancer or the advice of the physician to stop the treatment?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…characterised by similar healthcare utilisation, medical conditions and diabetes duration or severity) and use appropriate methods to account for confounding, such as propensity score methods. In spite of the methodological issues identified in this review, and illustrated in this text, improper practices with regard to study design and analysis persist in observational studies that attempt to assess the effect of glucose-lowering medications on other clinical outcomes as well [129][130][131][132]. Greater attention to the principles described in this paper would serve to address certain research practices that are particularly susceptible to spurious findings and may mislead the medical community.…”
Section: Confoundingmentioning
confidence: 93%
“…Despite the logistic challenges, trials should incorporate companion translational research, bearing in mind that the cost of these studies is small relative to the overall cost of trial execution, yet the information gained can be strategically important. Although the private sector has had limited involvement in studies of metformin in view Work is underway to interpret retrospective data in a manner that minimizes possible biases (114), and analysis of cancer incidence in cohorts where metformin use for diabetes treatment or prevention was randomized will be important.…”
Section: Challenges For Future Researchmentioning
confidence: 99%